Supporting ageing with a positive psychological framework and tools - Kun, Agota (Magyar Gerontológia, 2022)
In the classical literature, but also in the everyday approach, ageing is mostly associated with decline, deterioration of various skills, abilities, capacities, mental dysfunction, increasing inactivity, shrinking relationships and similar, more negative characteristics. We think of ageing as if it were a necessarily negative, unavoidable and unavoidable deterioration - but one that we must accept passively, at the same time - at the physical, mental and psychological levels. The presentation will focus on the reinterpretation offered by a positive psychology approach, pointing out that the second half of life is not necessarily about decline, mental problems, dissatisfaction or bitterness, but can also be about fulfilment, happiness, discovering and exploiting new potentials and strengths, new goals and living a truly fulfilling life. What is at stake to make this happen? How can we support this with the tools of positive psychology? The presentation will not be about anti-ageing tips, but about how to promote mental health in later life so that we can live ourselves and our lives to the full in this period of life with a positive outlook. The focus will be on the how, so the knowledge and a possible toolkit of interventions will be presented.